Biocontrol of Aspergillus Species on Peanut Kernels by Antifungal Diketopiperazine Producing Bacillus cereus Associated with Entomopathogenic Nematode - Kumar, Sasidharan Nishanth (Public Library of Science, 2014)
The rhabditid entomopathogenic nematode associated Bacillus cereus and the antifungal compounds produced by this bacterium were evaluated for their activity in reducing postharvest decay of peanut kernels caused by Aspergillus species in in vitro and in vivo tests. The results showed that B. cereus had a significant effect on biocontrol effectiveness in in vitro and in vivo conditions. The antifungal compounds produced by the B. cereus were purified using silica gel column chromatography and their structure was elucidated using extensive spectral analyses. The compounds were identified as diketopiperazines (DKPs) [cyclo-(L-Pro-Gly), cyclo(L-Tyr-L-Tyr), cyclo-(L-Phe-Gly) and cyclo(4-hydroxy-L-Pro-L-Trp)]. The antifungal activities of diketopiperazines were studied against five Aspergillus species and best MIC of 2 µg/ml was recorded against A. flavus by cyclo(4-hydroxy-L-Pro-L-Trp). To investigate the potential application of cyclo(4-hydroxy-L-Pro-L-Trp) to eliminate fungal spoilage in food and feed, peanut kernels was used as a food model system. White mycelia and dark/pale green spores of Aspergillus species were observed in the control peanut kernels after 2 days incubation. However the fungal growth was not observed in peanut kernels treated with cyclo(4-hydroxy-L-Pro-L-Trp). The cyclo(4-hydroxy-L-Pro-L-Trp) was nontoxic to two normal cell lines [fore skin (FS) normal fibroblast and African green monkey kidney (VERO)] up to 200 µg/ml in MTT assay. Thus the cyclo(4-hydroxy-L-Pro-L-Trp) identified in this study may be a promising alternative to chemical preservatives as a potential biopreservative agent which prevent fungal growth in food and feed. To the best of our knowledge, this is the first report demonstrating that the entomopathogenic nematode associated B. cereus and cyclo(4-hydroxy-L-Pro-L-Trp) could be used as a biocontrol agents against postharvest fungal disease caused by Aspergillus species.